Analisis Kemampuan Pemecahan Masalah Matematis : Dampak Blended Learning Menggunakan Edmodo - Noviyanti, Fifit; Sugiharta, Iip; Farida, Farida (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research is based on the background of the low mathematical problem solving abilities due to less effective learning, especially lack of lesson hours. Blended learning is a two-way learning model namely face-to-face learning and online learning, while E-learning is a face-to-face learning model. The blended learning and e-learning learning model requires online media such as Edmodo. Efforts to address these problems, researchers aim to determine the effect of these two learning on improving mathematical problem solving abilities. The research method used in this study uses quasi-experimental methods (Quasy experimental design) with the type of research used is the pretest-posttest control group design. The data collection technique uses a randomized class technique, where the population is all eighth grade students of SMP N 21 Bandar Lampung. The hypothesis test used is gain-test with analysis techniques using one way ANOVA. From the results of the study, blended learning and e-learning using edmodo there was an increase in mathematical problem solving skills with moderate levels of calcification.